Soluções estratégicas com foco na melhoria da produtividade para criação de valor em uma empresa do setor de Tecnologia da Informação - Rodrigues, Andrea Cristina Deis (2019)
This paper presents an account of the work performed in a software development and implementation company applied to the management of processes and operations of companies operating in various business sectors for the automation of administrative, commercial, financial and industrial actions. The objective of this work was to identify and propose ways to increase management effectiveness and improve productivity, taking advantage of strategic opportunities for creating value for customers and developing business. The analysis of environmental trends and the current and required resources and capacities to increase the participation and offer of value to the market was carried out, seeking to know the context in which the company operates and possible problems that make it difficult to take advantage of potential opportunities of development. For analysis and diagnosis of the situation, we dealt with the complexity that involves variables such as human behavior, communication barriers, access to information and market dynamics. The diagnosis contemplated the understanding of the logic of the business, its value proposition, to which public and customer segments, through which channels of relationship and distribution, activities, resources and partnerships required, also contemplating the equation of costs and revenues of the operation. As a result, a set of strategic drivers for the business was elaborated, associated to a proposal applied to the adaptation of the organizational behavior to the identified demands for the attainment of the desired results. Business development resulting from efficiency and effectiveness gains in the decision-making process, the use of opportunities with innovation and internal process structure represent a significant contribution of the application of this work to the focused organization. Sharing experience through this report tends to influence the development of management technology as a replicable example in similar situations. It is hoped, also, to contribute to the economic and social development, directly affected by the prosperity of the businesses that meet the needs of the community, as the one that represents the case that was object of the present work.